2013
DOI: 10.1371/journal.pone.0069347
|View full text |Cite
|
Sign up to set email alerts
|

A Role for MeCP2 in Switching Gene Activity via Chromatin Unfolding and HP1γ Displacement

Abstract: Methyl-CpG-binding protein 2 (MeCP2) is generally considered to act as a transcriptional repressor, whereas recent studies suggest that MeCP2 is also involved in transcription activation. To gain insight into this dual function of MeCP2, we assessed the impact of MeCP2 on higher-order chromatin structure in living cells using mammalian cell systems harbouring a lactose operator and reporter gene-containing chromosomal domain to assess the effect of lactose repressor-tagged MeCP2 (and separate MeCP2 domains) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In humans, loss of function mutations in the X chromosome-linked gene MECP2 cause the neurodevelopmental disorder Rett Syndrome (RTT) (Amir et al, 1999). MECP2, the protein product of MECP2, binds to methylated DNA (Lewis et al, 1992) and controls transcriptional programs by modifying chromatin structure (Skene et al, 2010;Agarwal et al, 2011;Brink et al, 2013;Maxwell et al, 2013). The vast majority of humans with RTT are females with a heterozygous loss of function mutation who are therefore mosaic for the gene (Van den Veyver and Zoghbi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, loss of function mutations in the X chromosome-linked gene MECP2 cause the neurodevelopmental disorder Rett Syndrome (RTT) (Amir et al, 1999). MECP2, the protein product of MECP2, binds to methylated DNA (Lewis et al, 1992) and controls transcriptional programs by modifying chromatin structure (Skene et al, 2010;Agarwal et al, 2011;Brink et al, 2013;Maxwell et al, 2013). The vast majority of humans with RTT are females with a heterozygous loss of function mutation who are therefore mosaic for the gene (Van den Veyver and Zoghbi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During development, MeCP2 mutant mice exhibit increased levels of histone H1 that may partially compensate for the loss in MeCP2, and as such explain for delay in major disease phenotypes to the postnatal stage (Skene et al, 2010). Recent evidence indicated that MeCP2 can not only induce chromatin compaction, but that targeted binding of MeCP2 to specific loci may elicit extensive chromatin unfolding (Brink et al, 2013). In addition, MeCP2 known protein interactors connect it to repression or to activation of transcription (Nan et al, 1997; Jones et al, 1998; Chahrour et al, 2008; Kim et al, 2013; Lyst et al, 2013; Maxwell et al, 2013; Lyst and Bird, 2015; Mahgoub et al, 2016; Ludwig et al, 2017; Rajavelu et al, 2018), RNA splicing (Jeffery and Nakielny, 2004; Maunakea et al, 2013; Li et al, 2016; Cheng et al, 2017; Wong et al, 2017; Zheng et al, 2017), as well as microRNA binding (Khan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…26 AT-Hook motifs within the TRD contribute to nonspecific binding and chromatin restructuring. 10,21,2729 Disruption of a highly conserved AT-hook alters chromatin compaction, causing neurological dysfunction. 28 The effects of MeCP2 mutations outside MBD are dose-dependent; a single copy of wild-type MeCP2 can restore normal development.…”
mentioning
confidence: 99%
“…3137 MeCP2 functions in competition with linker histones, 38,39 whose interaction with DNA is mostly electrostatic. 27 Thus, ionic changes have the potential to regulate the partitioning of MeCP2 between specific and nonspecific sites on chromatin and exchange of MeCP2 with linker histones.…”
mentioning
confidence: 99%